Brucella abortus: pathogenicity and gene regulation of virulence - Rivas-Solano, Olga (2015)
Brucella abortus is a zoonotic intracellular facultative pathogen belonging to the subdivision α2 of class Proteobacteria. It causes a worldwide distributed zoonotic disease called brucellosis. The main symptoms are abortion and sterility in cattle, as well as an undulant febrile condition in humans. In endemic regions like Central America, brucellosis has a high socioeconomic impact. A basic research project was recently conducted at the ITCR with the purpose of studying gene regulation of virulence, structure and immunogenicity in B. abortus. The present review was written as part of this project. B. abortus virulence seems to be determined by its ability to invade, survive and replicate inside professional and non-professional phagocytes. It reaches its intracellular replicative niche without the activation of host antimicrobial mechanisms of innate immunity. It also has gene regulation mechanisms for a rapid adaptation to an intracellular environment such as the two-component signal transduction system BvrR/BvrS and the quorum sensing regulator called Vjbr, as well as other transcription factors. All of them integrate a complex gene regulation network.